Peningkatan Kesejahteraan Masyarakat melalui Kelompok Tani Hutan: Studi Kasus di Dukuh Karanguluh Karanganyar - Agustina, Ana; Nayasilana, Ike Nurjuita; Pertiwi , Yus Andhini Bhekti; Rahmadwiati, Rissa; Wicaksono, Rezky Lasekti (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2024)
Forest Farmer Group (KTH) is a platform which facilitates the establishment of enterprises by communities residing near forests. The KTH Harapan Makmur, situated in Gempolan Village, Karanganyar Regency, Central Java, has the capacity to harness both human resources and natural resources. Nevertheless, when it comes to organizational development, it lies short of being ideal. Therefore, it is imperative to offer support linked to enhancing institutional capacity. The objective of this action is to enhance community awareness of growing organizations. A community service event took place in July 2023, attended by representatives from the Gempolan Village Government, forestry extension workers, a community service team from Universitas Sebelas Maret, and members of the KTH Harapan Makmur. The activity was implemented through the organization of a Focus Group Discussion (FGD) primarily aimed at facilitating the compilation of the AD/ART. Attending participants were requested to complete a questionnaire. The activity findings indicate that roughly 40.9% of KTH Harapan Makmur members are employed as farmers, earning a monthly income ranging from less than 1 million rupiah to 3 million rupiah. Following the session, participants' understanding of KTH exhibited a percentage gain in comparison to their level of knowledge before the activity. Thus far, the primary obstacle has been the procurement of capital sources, which remain restricted. Engagement in diverse activities is expected to create possibilities for collaboration and capital acquisition to ensure the long-term viability of KTH's business.